MARARI SABTU DALAM UGAMO MALIM PADA KOMUNITAS PARMALIM DI KOTA MEDAN - Kori Insani; Mhd. Syahminan; Muhammad Jailani (UIN Sumatera Utara Medan, 2021)
This study aims to determine the process of the Marari Saturday ritual ceremony and to find out the impact or influence of Marari Saturday in the lives of the people of Ugamo Malim adherents. In this study, the author uses a qualitative method with a descriptive approach. And the theory used in this study uses the structural-functional theory proposed by Bronislaw K. Malinowski. The process of collecting data using observation, direct interviews accompanied by documentation. From the results of the research, it is known that the Saturday Marari process is an action that is usually carried out by Parmalim people to honor Ompung Debata Mulajadi Nabolon. Every Saturday, Parmalim parishioners gather at a predetermined place in the Medan City branch, namely Bale Parsantian to worship and be grateful for Ompung Debata Mulajadi Nabolon and at that time these individuals are given poda or directions to be more firm in their behavior in carrying out their Ugamo . In the ritual ceremony of Marari Saturday, it is influential in the life of the people of Ugamo Malim followers. Which is influential in social life, such as, influencing social ties or solidarity that exists between fellow adherents and local residents and can be useful for those around them, in religious life it affects the life of community harmony and blessings in carrying out the life given by Ompung Debata Mulajadi Nabolo, especially the community. Parmalim. In economic life, it affects the lives of its adherents, and in Parmalim's teachings, Patik ordered his followers to work hard, think logically, and not expect the mercy of others. And in the field of education, the ritual ceremony of the Saturday Marari has a fairly important influence, because Parmalim always emphasizes that knowledge is very much needed in the development of the education of its adherents.